2022
DOI: 10.3390/diagnostics12030663
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease Defined by Fatty Liver Index and Incidence of Heart Failure in the Korean Population: A Nationwide Cohort Study

Abstract: Fatty liver index (FLI) is a simple and useful index that evaluates non-alcoholic fatty liver disease (NAFLD), particularly in large epidemiologic studies. Heart failure (HF) is becoming a burden to public health as the global trend toward an aging society continues. Thus, we investigated the effect of FLI on the incidence of HF using large cohort data from the Korean National Health Insurance health database. Methods and Results: A total of 7,958,538 subjects aged over 19 years without baseline HF (men = 4,14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Estimated glomerular filtration rate (eGFR) was calculated using the equation from the Modification of Diet in Renal Disease study: eGFR=175×serum creatinine -1.154 ×age -0.0203 , and was further multiplied by 0.742 for women [ 19 ]. The fatty liver index (FLI) was used to access the degree of fatty liver and was calculated as reported in a previous study [ 20 ]. Participants were defined as having fatty liver if their FLI was ≥60.…”
Section: Methodsmentioning
confidence: 99%
“…Estimated glomerular filtration rate (eGFR) was calculated using the equation from the Modification of Diet in Renal Disease study: eGFR=175×serum creatinine -1.154 ×age -0.0203 , and was further multiplied by 0.742 for women [ 19 ]. The fatty liver index (FLI) was used to access the degree of fatty liver and was calculated as reported in a previous study [ 20 ]. Participants were defined as having fatty liver if their FLI was ≥60.…”
Section: Methodsmentioning
confidence: 99%
“…The study found that patients with the highest fatty liver index (FLI) score independently (HR between Q4 and Q1 2.709, 95% CI 2.380–3.085) suffered from a higher risk of new‐onset heart failure, compared with patients with the lowest FLI 33 . Likewise, during a mean follow‐up of 8.26 years in a Korean nationwide cohort study with 7,958,538 participants aged over 19 years without baseline heart failure, researchers unveiled that FLI ≥ 60 increased HR for incident heart failure (HR 1.493, 95% CI 1.41–1.581), compared with the FLI < 30 41 …”
Section: The Epidemiological Pattern Of Cardiovascular Events In Pati...mentioning
confidence: 99%
“…The purpose of this study was to examine the association between alcohol consumption and MASLD in Korean men using the lipid accumulation product (LAP) score as a noninvasive marker of MASLD risk while considering their facial flushing response [ 10 , 11 , 12 , 13 ]. We hypothesized that the alcohol flushing response, influenced by genetic variations in alcohol-metabolizing enzymes, may modify the relationship between alcohol consumption and MASLD risk, leading to different outcomes in individuals with and without flushing [ 14 ].…”
Section: Introductionmentioning
confidence: 99%